10-band graphic equalizer - Francis Abligado, Bujet (Universiti Malaysia Sarawak, UNIMAS, 2000)
Graphic Equalizer (EQ) is an electronic project that has help to overcome the problem encountered by those who interested to produce a better sound quality from their sound system. This report consists of the overview of a 10-band graphic equalizer and also the literature review of it.